Tumour necrosis factor haplotypes associated with sensory neuropathy in Asian and Caucasian human immunodeficiency virus patients - Chew, C.; Cherry, C.; Imran, D.; Yunihastuti, E.; Kamarulzaman, A.; Varna, S.; Ismail, R.; Phipps, M.; Aghafar, Z.; Gut, I.; Price, Patricia (2011)
In human immunodeficiency virus (HIV) patients, neuropathy is a common adverse side effect to some antiretroviral treatments, particularly stavudine. As stavudine is cheap, it is widely used in Asia and Africa. We showed that increasing age and height moderately predict the development of neuropathy. This was improved by the inclusion of tumour necrosis factor (TNF)-1031 (rs1799964). To investigate this association, Malay (n = 64), Chinese (n = 74) and Caucasian patients (n = 37) exposed to stavudine were screened for neuropathy. DNA samples were genotyped for polymorphisms in the central major histocompatibility complex (MHC) near TNF, and haplotypes were derived. The haplotype group FVa6,7,8 (incorporating TNF-1031) was found to be associated with neuropathy in Chinese patients in bivariate analyses (P = 0.03), and in Malays and Chinese in a multivariate analysis correcting for age and height (P = 0.02, P = 0.03, respectively). This trend was also confirmed in Caucasians. © 2010 John Wiley & Sons A/S.